Model validation of the output reciprocating dynamic responses of a twin electro-rheological (ER) clutch mechanism - Tan, K.P.; Johnson, A.R.; Stanway, R.; Bullough, W.A. (Mechanism and machine theory, 2007)
Electro-rheological (ER) fluid devices are becoming more popular in the industrial applications. This is due to the fast speed of response and large output dynamics of the ER actuators. The usefulness of this ER dynamic response is considered in the material winding processes where fast output bi-directional responses are essential. Therefore in the present paper, an ER twin clutch mechanism is proposed. This clutch mechanism consists of two identical clutches that rotate in opposite directions. But the bi-directional output dynamics of the clutch mechanism is not well understood due to its non-validation in the past. The main aim of this paper is to model the reciprocating responses of the clutch mechanism and then perform model validation with the measured test results. The close agreements between the modeled and experimental data indicate that the ER output angular velocity and displacement responses’ models of the clutch mechanism are validated. These validated models can then be used to predict accurately the reciprocating output responses of the twin ER clutch mechanism for future research studies.